2015
DOI: 10.1155/2015/197521
|View full text |Cite
|
Sign up to set email alerts
|

High‐Salt Enhances the Inflammatory Response by Retina Pigment Epithelium Cells following Lipopolysaccharide Stimulation

Abstract: High-salt has been shown to play a role in the pathogenesis of autoimmune disease. In this study, we investigated the effect of high-salt on the production of inflammatory mediators by ARPE-19 cells and the possible mechanisms involved. ARPE-19 cells were cultured with LPS in DMEM to which extra NaCl had been added (20 mM and 40 mM). NaCl had no influence on the apoptosis and proliferation of ARPE-19. Addition of 40 mM NaCl significantly induced IL-6 and MCP-1 production but had no effect on IL-8 secretion. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
(48 reference statements)
2
14
0
Order By: Relevance
“…These findings were subsequently confirmed by independent research groups [73, 74]. Moreover, this enhanced pro-inflammatory activation is also present in retina pigment epithelium cells [75]. Mechanistically, high salt-boosted macrophage activation required p38/MAPK and downstream NFAT5-signaling, but it was independent of signal transducer and activator of transcription (STAT) 1-signal transduction [57].…”
Section: A High Salt Level Augments Pro-inflammatory and Antimicrobiamentioning
confidence: 70%
“…These findings were subsequently confirmed by independent research groups [73, 74]. Moreover, this enhanced pro-inflammatory activation is also present in retina pigment epithelium cells [75]. Mechanistically, high salt-boosted macrophage activation required p38/MAPK and downstream NFAT5-signaling, but it was independent of signal transducer and activator of transcription (STAT) 1-signal transduction [57].…”
Section: A High Salt Level Augments Pro-inflammatory and Antimicrobiamentioning
confidence: 70%
“…Indeed, a number of reports in the literature indicate that the addition of salts or other osmotic agents to the cell environment may induce the production of inflammatory cytokines (20,(39)(40)(41)(42)(43)(44). These studies indicate that the development of inflammation as a consequence of osmotic stress may be a general phenomenon affecting PBMCs (44,45) and a number of other cell types (46)(47)(48)(49)(50). Both lower (20 mM to 41 mM) (48) and higher (100 mM to 135 mM) (47) concentrations of NaCl than the amount tested in the present study (65 mM) have been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Also, increased levels of pro‐inflammatory cytokines and increased activation of nuclear factor kappa B were observed in salt‐treated macrophages . Zhang et al found that high salt treatment significantly enhanced production of IL‐6 and monocyte chemoattractant protein‐1 in retinal pigment epithelium cells in vitro . Also, co‐culture of the cells with NaCl led to upregulation of the transcription factors, SGK1 and NFAT5, and significant increases of p38 MAPK, Akt and nuclear factor kappa B phosphorylation in vitro .…”
Section: High Salt Intake Inflammation and Autoimmunity: In Vivo Andmentioning
confidence: 99%
“…Zhang et al found that high salt treatment significantly enhanced production of IL‐6 and monocyte chemoattractant protein‐1 in retinal pigment epithelium cells in vitro . Also, co‐culture of the cells with NaCl led to upregulation of the transcription factors, SGK1 and NFAT5, and significant increases of p38 MAPK, Akt and nuclear factor kappa B phosphorylation in vitro . In contrast, higher salt treatment restrains the activities of regulatory T cells (Treg) and immunoregulatory cytokines, such as IL‐13 and IL‐4 .…”
Section: High Salt Intake Inflammation and Autoimmunity: In Vivo Andmentioning
confidence: 99%